2004
DOI: 10.3758/bf03196038
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the rabbit’s conditioned nictitating membrane response without direct reinforcement after extinction

Abstract: Three experiments demonstrated that, following the extinction of an established conditioned stimulus (CSA--e.g., tone), the pairing of a novel, cross-modal stimulus (CSB--e.g., light) with the unconditioned stimulus (US) results in strong recovery of responding to the extinguished CSA. Experiment 1 demonstrated that the recovery of responding to CSA is not the result of US reinstatement but is attributable to pairings of CSB with the US. Experiment 2 demonstrated that the recovery of responding is specific to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 50 publications
4
48
2
Order By: Relevance
“…First, the test trials at the beginning of the very first session of Lϩ training provided an estimate of any residual spontaneous recovery of extinguished responding to T1. Second, the test trials at the start of the remaining sessions of Lϩ training allowed us to confirm that the recovery of responding is independent of any immediate aftereffects of training with the Lϩ trials and is retained from a previous session (Weidemann & Kehoe, 2004).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…First, the test trials at the beginning of the very first session of Lϩ training provided an estimate of any residual spontaneous recovery of extinguished responding to T1. Second, the test trials at the start of the remaining sessions of Lϩ training allowed us to confirm that the recovery of responding is independent of any immediate aftereffects of training with the Lϩ trials and is retained from a previous session (Weidemann & Kehoe, 2004).…”
Section: Methodsmentioning
confidence: 97%
“…However, research in our laboratory has not revealed that reinstatement occurs in the rabbit NM preparation (Napier et al, 1992;Weidemann & Kehoe, 2004). Even repeated presentations of the US, which could cause reacquisition of context-US associations (Brandon & Wagner, 1991;Wagner & Brandon, 1989), do not result in discernible reinstatement of the CR to an extinguished CS (Weidemann & Kehoe, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations